The Influence Of Product And Service Innovation On Marketing Management Success In Global Competitive Markets - Dalimunthe, Theresia Josephin (Mutiara: Multidiciplinary Scientifict Journal, 2025)
In a progressively competitive global environment, organizations must continually reinvent their products and services to sustain their competitive advantage and achieve success in marketing management. Product innovation enables companies to generate additional value, distinguish themselves from rivals, and address the changing demands of the market. Concurrently, service innovation improves client experience, fortifies loyalty, and broadens market reach. This study seeks to investigate the degree to which product and service innovation impacts the efficacy of marketing management in internationally competitive markets. A quantitative methodology was utilized, employing survey data gathered from global corporations across diverse industry sectors. The analysis indicates a substantial association between innovation levels and the attainment of marketing objectives, with service innovation serving as a mediating role in the efficacy of product strategies. The research emphasizes the necessity of synchronizing innovation with marketing initiatives as a crucial element in creating durable competitive advantages. These findings provide strategic insights for marketing managers aiming to implement adaptable and innovative strategies to address the challenges posed by changing customer demands and global market dynamics.